Literature as dialogue : invitations offered and negotiated - Sell, Roger D. (Dialogue studies ;, 2014)
How is it that some texts achieve the status of literature? Partly, at least, because the relationship they allow between their writers and the people who respond to them is fundamentally egalitarian. This is the insight explored by members of the Åbo literary communication network, who in this new book develop fresh approaches to literary works of widely varied provenance. The authors examined have written in Ancient Greek, Táng Dynasty Chinese, Middle, Modern and Contemporary English, German, Romanian, Polish, Russian and Hebrew. But each and every one of them is shown as having offered thei.